The impact of cultural origin on the psychiatric expertise in Switzerland: a focus on sexual violence illustrated by two criminal cases - Marco De Pieri; Neva Suardi (Frontiers in Psychiatry)
Cultural biases and integration in novel socio-geographic contexts are relevant factors for the understanding of dynamics beneath sexual violence, and possibly play a role in modifying responsibility and perpetrators treatment. Here we offer a conceptual analysis of the relevant literature and two case study. Cultural factors influence power dynamics and individual values, impacting the occurrence of sexual violence; the understanding of “coercion” varies across cultures, and cultural legitimization may ensue. The consequences of sexual assault also differ, with shame prevailing in socio-centric societies and guilt in ego-centric societies. Rape and gender-based violence is influenced by masculinity and femininity concepts, the former identified with power. Dominance, rather than sexual gratification, can lead to sexual violence, which could also be a “male backlash” against gender equality. Biological theories link sexual violence to genetic factors; a psychodynamic perspective suggests an unconscious social reproduction of masculine culture and delves into possible explanations for violent behavior. Acculturation strategies and acculturative stress are explored, with a focus on Berry’s strategies and on Camilleri’s model of identity in intercultural situations. The impact of cultural factors on responsibility is discussed, highlighting variability in criminal laws and attitudes towards cultural offenses in different countries. The analysis of two criminal cases accused of rape, revealed common and diverging elements. Both individuals come from favorable socio-economic backgrounds, and lacked of prior or present psychiatric diagnoses. Integration difficulties, psychosexual attitudes, and the improper application of cultural codes played a crucial role. In conclusion, anthropological and ethnopsychiatric knowledge should be integrate into forensic assessments. Early detection of non-acculturation elements is need to prevent criminal behaviors, and a diagnostic instrument as a validated rating scale should be implemented.